Exchange Character of Caesium Ions onto Zirconium Tungstate - R.R. Sheha; S.H. El-Khouly (Adsorption Science & Technology)
Amorphous zirconium tungstate, an inorganic ion-exchanger, was synthesized under optimum conditions and used as a cation-exchange material for the removal of caesium ions from radioactive waste solutions under simulated conditions using batch techniques. The physical and chemical properties of the synthesized ion-exchanger were characterized using Fouriertransform (FT) infrared, X-ray diffraction (XRD) and differential scanning calorimetric (DSC) techniques. Its chemical stability in various mineral acids, bases and organic solvents was also assessed. The data obtained reveal that the prepared exchanger had a good ionexchange capacity (1.34 mequiv/g towards Cs + ions) and a high thermal and chemical stability. A hypothetical structural formula, Zr[WO 2 (OH) 2 ]• 4H 2 O, was proposed on the basis of chemical composition, FT-IR and thermal analyses. The influences of pH, contact time, initial solute concentration and temperature are reported. Various parameters such as the effective diffusion coefficient under different conditions and the activation energy were determined from the graphical representation of the linearized form of the Arrhenius equation. Thermodynamic parameters such as ΔG 0 , ΔH 0 and ΔS 0 were also calculated. The numerical value of ΔG 0 increased from 7.43 to 9.74 kJ/mol as the temperature was increased from 298 K to 313 K, indicating that the exchange reaction was more favourable at low temperatures. The negative value of ΔH 0 (–49.55 kJ/mol) reflected the exothermic nature of the exchange process.